Occurrence of Porodaedalea pini (Brot.: Fr.) Murr. in pine forests of the lake district in south-western Turkey - Lehtijärvi, A.; Lehtijärvi, H.T.D. (Phytopathologia Mediterranea, 2007)
The occurrence of basidiocarps of the white rot fungus Porodaedalea (Phellinus) pini on Pinus nigra subsp. pallasiana and P. brutia was investigated in six stands, covering a total land area of some 650 hectares, in Isparta province of the Lake District in Turkey. The height above ground of the lowermost P. pini basidiocarp was measured on each trunk. Basidiocarps of P. pini were found on thirty-eight trees, 32 P. nigra subsp. pallasiana (84.2% of the total) and six P. brutia (15.8%). The breast-height diameter of P. nigra individuals with P. pini ranged from 41 to 188 cm (average 77.7 cm) and that of P. brutia with P. pini from 68 to 96 cm (average 76.4 cm). Basidiocarps were mostly found on the lower part of the trunks of old trees. In addition to pathological aspects, the ecological role of the fungus in old-growth pine forests is discussed in relation to nature conservancy and biodiversity.